Textual and discoursal strategies of national leaders to establish their political images in the global arena - Diah Kristina; Ni Luh Putu Setiarini; Muhammad Thoyibi (Universitas Syiah Kuala, 2021)
Giving speeches is one’s vital competency for creating a country’s image in the global arena. Every political speech represents the speaker’s deliberative reasoning to respond to the existing situation and is a synoptic lens of the intended judgment on particular issues. This study explores three Indonesian speakers’ textual and discoursal strategies in the opening of three political speeches. By employing qualitative research, the researchers analyzed the textual and discoursal properties in terms of features, characters, and structures of argumentation and the speakers’ flow of thinking realized linguistically. This research found that the speeches’ micro and macro components are in mutual supporting functions to accommodate the themes of the discourse. Verbally, each speaker built their image as a figure who concerns solidarity, a leader who is aware of the global crisis, and an activist who promotes Indonesia’s positive global roles. The findings imply the pivotal roles of textual and discoursal strategies to construct the national and personal image of a politician delivering a speech for the global audience. This study is expected to be beneficial for ESP, especially for the teaching of English for Public Relations.